Optimising bromelain milk clotting activity from josapine pineapple peel extract for soft cheese production / Muhammad Yazid Abd Halim - Abd Halim, Muhammad Yazid (2024)
During canning and juice processing of pineapple, pineapple peel usually discharged. Discharged of pineapple peel during this production will produce a lot of waste. In industrial practices, pineapple waste is either used as animal feed or disposed to the soil as waste. Pineapple peel contain valuable natural enzyme which is bromelain. Bromelain is enzyme which believed to have many benefits and very promising to the development of food and pharmaceutical industries. The purpose of this study is to determine the milk clotting and physicochemical properties of soft cheese made using bromelain extracted from pineapple peel variety Josapine. Purified bromelain powder from pineapple peel was produced through purification process. These include extraction from pineapple peel using purified water as a medium extraction, purification by ammonium sulphate precipitation, desalting using continuous diafiltrator and followed by freeze drying. Each step was found to produce different effect on bromelain activity, protein content, specific enzyme activity and purification level. It was found that it is best to store the bromelain powder at frozen temperature (-20oc) because its bromelain activity could only loss 10.34% up to one month storage time for maturity index 2. Thus, maturity index 2 was chosen for optimisation step. The optimisation condition for milk clotting activity of bromelain during the production of soft cheese using Response Surface Methodology (RSM) was found with bromelain concentration of 0.53%, incubation temperature of 54.2oc and incubation time of 2.33 hours. It was found that the rheological properties of soft cheese made from pineapple peel and bromelain standard shows a non-Newtonian Pseudoplastic behaviour (shear-thinning). Meanwhile, for the proteolysis of soft cheese using SDS PAGE found that the molecular weight for α, β and κ casein was around 30 kda. In conclusion, the bromelain enzyme extracted from pineapple peels variety Josapine has a potential to be utilized as milk clotting enzymes especially in the production of soft cheese.